Aphid species populations and their seasonal fluctuation in Prunus orchards affected by Sharka disease within the quarantine areas of Argentina - Mazzitelli, Emilia; Dal Zotto, Angelica; Piglionico, Damián Gustavo; Farrando, Roberto Jes; Porcel, Laura Beatriz; Ojeda, Eva Maria; Raigon, Juan Manuel; Marini, Diana Beatriz (Sociedad Entomológica Argentina, 2024)
Sharka is a disease of stone fruits, produced by the Plum Pox Virus and transmitted by aphids. It was detected for the first time in Argentina in 2004. In order to assess the aphid species that could act as a potential vector of this disease, we described the aphids community and seasonal fluctuation within two Prunus orchards affected by Sharka disease, located within two quarantine areas in Cuyo Region. Aphids were trapped weekly from October (spring) to April (autumn) during 2011-2012 and 2012-2013, by using yellow water traps (TAA), and identified using winged aphid’s taxonomic keys. In total, 27 aphid species were identified. The most dominant species collected was Myzus persicae (Sulzer). Orchard-trapped population of this dominant aphid showed seasonal fluctuation with two peaks, November (spring) and March (autumn).